Thermally releasable multilayer composition bonded to thermoplastic primer

By introducing a thermoplastic primer layer into the multi-layer composition, the problem of difficulty in removing the thermosetting adhesive layer and the substrate is solved, and the adhesive layer is removed without damage at high temperatures while maintaining the room temperature. Bonding strength.

CN119487142APending Publication Date: 2025-02-18DOW GLOBAL TECHNOLOGIES LLC +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202280097008.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-06-30
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove bonding between the thermosetting adhesive layer and the substrate without damaging the adhesive components, especially in the case of high surface area attachment and wide operating temperature range.

Method used

Multilayer compositions containing a thermoplastic primer layer softened or melted within a temperature range of 50°C to 130°C to facilitate the separation between the thermosetting adhesive layer and the substrate.

Benefits of technology

Detachment of the thermosetting adhesive layer without damage at high temperatures is achieved, bonding strength at room temperature is maintained, and shear and tensile strength reductions are reduced without the thermoplastic primer layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005181754050000031
    Figure BDA0005181754050000031
  • Figure BDA0005181754050000081
    Figure BDA0005181754050000081
  • Figure BDA0005181754050000091
    Figure BDA0005181754050000091
Patent Text Reader

Abstract

The multilayer composition includes: a substrate having a surface energy of 35 dynes / cm or more; one or more thermoplastic primer layers comprising from 55 wt% to 100 wt% of a maleic anhydride grafted chlorinated polyolefin and having a glass transition temperature in the range of from 50 DEG C to 120 DEG C; and one or more thermosetting adhesive layers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] Embodiments are directed to heat-releasable multi-layer compositions bonded with a thermoplastic primer layer and a thermosetting adhesive.

[0002] introduction

[0003] Thermoplastic adhesives and thermosetting adhesives are used in many industrial applications, including flexible packaging and mounting electric vehicle (EV) batteries. For most applications, thermosetting adhesives are selected based on bond strength, sub-state compatibility, and long-term durability under operating conditions. However, for many applications, the adhered components must be separated for the purpose of reusability, recyclability, maintenance or replacement of the parts. In order to detach EV battery cells bonded to a thermosetting adhesive layer, for example, physical removal methods such as prying, cutting or laser ablation are typically used. Other methods involve the use of solvents, alkalis or acids to remove thermosetting adhesives by immersion, which can produce chemical hazards and may provide limited penetration into the adhesive layer. Another problem with common detachment methods is their effectiveness at high surface area attachments (including those present in EV battery packs), which can cause damage to the adhered components. Summary of the invention

[0004] The multi-layer composition disclosed herein may include: a substrate having a surface energy of 35 dynes / cm or greater; one or more thermoplastic primer layers, the one or more thermoplastic primer layers comprising 55 wt % to 100 wt % of a maleic anhydride grafted chlorinated polyolefin and a glass transition temperature in the range of 50° C. to 120° C.; and one or more thermosetting adhesive layers. DETAILED DESCRIPTION

[0005] Embodiments are directed to heat-releasable multi-layer compositions for achieving release of high surface energy substrates by heating, these heat-releasable multi-layer compositions having one or more thermoplastic primer layers and one or more thermosetting adhesive layers. The thermoplastic primer layers disclosed herein can remain solid and maintain thermosetting adhesive properties throughout the operating temperature for most applications (e.g., up to 50° C.), but at temperatures near and above the glass transition temperature (T g ) or melting point temperature (T m ) at a temperature (e.g., in the range of 50°C to 130°C).

[0006] Electric vehicle battery designs typically include one or more battery packs containing multiple battery cells that are individually bonded to various types of substrates. EV batteries may also include a number of external features for protecting the battery pack and array of battery cells, including multiple housings and substrates. Due to the large surface contact area of ​​the battery components (e.g., approximately 0.5 m2 of a battery pack block), the battery pack may be bonded to a plurality of substrates.2 1.5m to the entire battery pack 2 ) and a wide operating temperature range (e.g., -20°C to 60°C), thermosetting adhesives are typically used to provide bonding strength between the battery and the underlying or overlying substrate and structure. However, the bonding strength of thermosetting adhesives makes it difficult to release the battery pack or battery pack substrate without damaging or deforming the adhered components.

[0007] The multi-layer compositions disclosed herein may incorporate one or more thermoplastic primer layers to mediate adhesion between a substrate (e.g., a battery cell) and a thermal management plate (e.g., a thermal or cooling sheet) or another substrate (e.g., a battery pack cover, a battery pack bottom) that enables release from the substrate upon application of heat, particularly for applications where thermosetting adhesives are typically used. The multi-layer compositions may incorporate a thermoplastic maleic anhydride grafted chlorinated polyolefin (MAH-g-CPO) that mediates adhesion of a thermosetting adhesive layer to a substrate having a surface energy greater than 35 dynes / cm.

[0008] The thermoplastic primer layer and the thermosetting adhesive layer disclosed herein can maintain good bond strength relative to the bond between the adhesive layer and the substrate without the primer layer. The multi-layer composition disclosed herein can reduce the lap shear strength at room temperature by less than 30% relative to the comparative multi-layer composition without the thermoplastic primer layer. The multi-layer composition disclosed herein reduces the cross-tension strength at room temperature by less than 30% relative to the comparative multi-layer composition without the thermoplastic primer layer.

[0009] The thermoplastic primer layer disclosed herein can be detachably bonded to the thermosetting adhesive layer and / or the substrate, so that the primer layer maintains bonding strength at a temperature equal to or lower than 50°C, but melts or softens at an elevated temperature to facilitate detachment. For example, at an elevated temperature (e.g., above 50°C), one (or more) thermoplastic primer layers melt or soften, thereby facilitating detachment between the thermoplastic primer layer and the substrate and / or the thermosetting adhesive layer. The thermoplastic primer layer disclosed herein can have a glass transition temperature (Tg) in the range of 50°C to 130°C, 50°C to 120°C, 55°C to 120°C, 55°C to 115°C, 55°C to 100°C, or 60°C to 80°C. g ).

[0010] The multilayer composition may include a high surface energy substrate on which one or more thermoplastic primer layers and / or thermosetting adhesive layers are formed, applied or deposited. The high surface energy substrate may include, for example, metal, epoxy or polyacrylate surfaces used in EV battery packs, thermal management panels and other industrial applications.

[0011] As used herein, "high surface energy substrate" refers to a substrate having a surface energy of 35 dynes / cm or greater, and does not include substrates with a surface free energy <35 dynes / cm. The high surface energy substrates disclosed herein include metals (such as aluminum, steel or alloys, zinc, etc.), non-metals (including glass, polar polymers (such as epoxy resins, polyurethanes, polyesters)), etc.

[0012] Table 1 includes additional examples of suitable high surface energy substrates. .

[0013]

[0014] In some cases, the high surface energy substrate may also be placed in contact with a multilayer composition containing one or more thermoplastic primer layers and / or thermosetting adhesive layers assembled on a second substrate or surface. In some cases, the multilayer composition may contain a thermoplastic primer layer contacting the high surface energy substrate and a thermosetting adhesive contacting the thermoplastic primer layer. The thermosetting adhesive may also mediate adhesion to a second substrate such as a thermal management plate.

[0015] In another example, the multilayer composition can contain a first thermoplastic primer layer contacting a high surface energy substrate and a thermosetting adhesive layer contacting the first thermoplastic primer layer. A second thermoplastic primer layer can contact the thermosetting adhesive layer and mediate adhesion to a second substrate.

[0016] The multilayer composition may include one or more thermosetting adhesive layers, which may include one or more polyurethanes, epoxy resins, polyacrylates, polyesters, cross-linked derivatives thereof, and the like. The thermosetting adhesive includes a polar thermosetting adhesive having a surface energy of 35 dynes / cm or greater. In an example, the thermosetting adhesive layer may include a 2K polyurethane structural adhesive based on diphenylmethane diisocyanate (MDI). The thermosetting adhesive disclosed herein may be water-based, solvent-based, or solvent-free.

[0017] The multi-layer composition disclosed herein may contain one or more thermoplastic primer layers comprising a maleic anhydride grafted chlorinated polyolefin (MAH-g-CPO) alone or in combination with another thermoplastic polymer. The maleic anhydride grafted chlorinated polyolefin disclosed herein may have a maleic anhydride grafting degree greater than 1% and a chlorination content greater than 10%. In some cases, the maleic anhydride grafted chlorinated polyolefin may have a chlorination degree of 10% to 30%, and / or at least one maleic anhydride degree of 1% to 5%. The maleic anhydride grafted chlorinated polyolefin disclosed herein may have a weight average molecular weight of 50,000 Da or greater, 60,000 Da or greater, or 100,000 or greater. The maleic anhydride grafted chlorinated polyolefin may have a weight average molecular weight in a range of 40,000 Da to 100,000 Da, 50,000 Da to 90,000 Da, or 50,000 Da to 80,000 Da.

[0018] The thermoplastic primer layer may contain a combination of MAH-g-CPO and one or more additional thermoplastic polymers, including thermoplastic polar polymers such as polyurethanes or polyesters, or less polar thermoplastic polymers such as maleic anhydride grafted polyolefins (MAH-g-POE), maleic anhydride grafted ethylene-vinyl acetate (MAH-g-EVA), ethylene-vinyl acetate (EVA), maleic anhydride grafted styrene-ethylene-butylene-styrene (MAH-g-SEBS), etc. The thermoplastic primer layer may comprise a polymer blend, including a combination of MAH-g-CPO and one or more additional polymers that change the overall polarity of the blended layer (e.g., a more or less polar polymer).

[0019] Introducing other polymer into the thermoplastic primer layer can change the polarity of primer layer and its compatibility with thermosetting adhesive layer or substrate, which can increase or reduce the corresponding interlayer bond strength at operating temperature. For example, increasing the polarity of thermoplastic primer layer can increase the compatibility with polar thermosetting adhesive layer, thereby increasing the bond strength at low temperatures. On the contrary, by blending MAH-g-CPO with a relatively low-polarity polymer in a thermoplastic primer layer, the compatibility with polar thermosetting adhesive layer will be reduced, thereby reducing bond strength and improving the breakaway performance at high temperatures.

[0020] Thermoplastic primer layers incorporating multiple polymers may include a MAH-g-CPO component in an amount of 55 wt% or greater, 60 wt% or greater, or 70 wt% or greater. Thermoplastic primer layers containing a resin mixture may include MAH-g-CPO and one or more thermoplastic polymer components in an amount of 0 wt% to 45 wt%, 0 wt% to 40 wt%, or 0 wt% to 30 wt%, with the balance being MAH-g-CPO and / or additives.

[0021] The thermoplastic primer layer can be applied to the adhesive layer and / or substrate layer in the form of a solid or film (e.g., 100 wt% solids). The thermoplastic primer layer can be produced by solvating the MAH-g-CPO resin (optionally with one or more additional thermoplastic polymers) in a suitable solvent and depositing the resulting solvated resin composition on a substrate or surface. The solvent is then evaporated when the thermoplastic primer layer is formed. Suitable solvents can vary depending on the solubility of the selected primer resin or resin mixture, and can include aqueous solvents or organic solvents. A mixture of non-polar and polar organic solvents can be used. Non-polar solvents can include cycloalkyl or aromatic substances, such as methylcyclohexane, toluene, etc. Polar organic solvents can include methyl ethyl ketone, ethyl acetate, butyl acetate, etc.

[0022] The organic solvated resin composition may include one or more primer resins (e.g., solids) in a weight percentage (wt%) ranging from 1 wt% to 35 wt%, 1 wt% to 20 wt%, or 3 wt% to 20 wt%. The organic solvated resin composition may include a non-polar organic solvent in a weight percentage (wt%) ranging from 60 wt% to 99 wt%, 65 wt% to 99 wt%, or 70 wt% to 99 wt%. The organic solvated resin composition may include a polar organic solvent in a weight percentage (wt%) ranging from 1 wt% to 40 wt%, 1 wt% to 45 wt%, or 1 wt% to 30 wt%.

[0023] The aqueous solvated resin composition may include one or more primer resins in a weight percentage (wt%) ranging from 15wt% to 65wt%, 20wt% to 60wt%, or 30wt% to 55wt%. The aqueous solvated resin composition may include an aqueous fluid in a weight percentage (wt%) ranging from 35wt% to 85wt%, 40wt% to 80wt%, or 45wt% to 70wt%.

[0024] The method for preparing the detachable multilayer composition disclosed herein can include providing a substrate surface, one or more thermoplastic primer layers and one or more thermosetting adhesive layers. The thermoplastic primer layer and the thermosetting adhesive layer can be prepared by solid deposition or by coating with a solvent composition using known methods (such as roller coating, flow coating, dip coating, spin coating, spray coating, blade coating and die coating). The multilayer composition disclosed herein can include a thermoplastic primer layer having a thickness in the range of 3 μm to 150 μm, 5 μm to 100 μm, or 8 μm to 90 μm. The layer thickness can be measured by any suitable method, including by PROGAGE ELECTROTECHNICALS, which can be purchased from Thwing-ALBERT Instrument Company. TM The layer thickness was measured using a thickness tester, in which the layer thickness was determined after drying for 1 day at room temperature.

[0025] A method of releasing a battery pack adhered to a substrate by a multilayer composition may include heating the multilayer composition to a "release temperature" above 50°C to induce softening or melting of the thermoplastic primer layer, followed by separation of one or more layers of the multilayer composition to release the battery pack from the substrate. The release method may include mechanically separating the primer and / or adhesive layer from the substrate layer by suitable techniques such as prying, wedging and / or impacting. In some cases, gravity or other "passive" techniques may be used to separate one or more layers of the multilayer composition.

[0026] Applying heat to the multilayer composition can include using an external heat source (such as an electric heating platform, an electric heating pad, an electric heating sheet, an electric heating blanket, etc.) or an internal heat source (such as a thermal management plate, a thermal management pad, an embedded heating element, etc.). Thermal management plates are typically used to maintain EV batteries within a stable temperature range (e.g., between -20°C and 50°C). During operation, the thermal management plate operates to dissipate or supply heat to the EV battery through passive (e.g., a heat sink) or active (e.g., using a flowing fluid or gas) heat transfer. The methods disclosed herein can utilize a thermal management plate or other method to directly heat the primer layer and the adhesive layer to a release temperature (i.e., above the transition temperature of the thermoplastic primer layer) while also minimizing heat transfer from the heat source to the battery pack and subsequent battery damage.

[0027] Detaching the substrate from the thermoplastic primer layer and the thermosetting adhesive layer can include heating the multilayer composition to a temperature equal to or greater than 50°C; and removing at least one of the layers of the multilayer composition. Methods of transferring heat can include heat management plates, ovens, heat guns, steam, microwave radiation, resistive heating, induction heating, and the like.

[0028] Solvent-based primers were prepared by dissolving primer resin particles in an 85:5 mixture of methylcyclohexane (MCH) and methyl ethyl ketone (MEK). The resin particles were added to a flask at a designed solid content (e.g., 1 wt%, 3.5 wt%, 5 wt%, 10 wt%, 15 wt%, and 20 wt%) and heated to 80°C with stirring until dissolved. After cooling to room temperature, the solvent-based primers were sealed and applied in the test.

[0029] In the tests, solvent-based primers are applied to substrates of different types and sizes, with the thickness of the primer layer controlled by the solids content of the primer or the application time. After drying, the surface-treated substrates are applied to lap shear strength, cross-tension strength or laboratory-established detachability tests.

[0030] The lap shear strength test was carried out according to GB / T 7124. The substrates tested included 3-type aluminum (3003), 3-type aluminum (3003) and 5-type aluminum (5754) coated with epoxy resin with a size of 25mm*100mm*1.5mm. The substrate surface was cleaned with ethanol and brushed with a primer layer sample solution and dried. A thermosetting adhesive was applied by mixing an isocyanate component and an isocyanate reactive component under vacuum conditions, and 0.5g to 1.5g of the adhesive was applied to the substrate. Along the length direction, a second substrate with the same bonding area was applied to the adhesive layer. Pressure was applied and the multilayer composition was cured at 23°C for 7 days. The lap shear strength was tested using an Instron test system.

[0031] The cross tensile strength test was carried out according to GB / T 6329. The substrate of the test includes 3-type aluminum (3003) coated with epoxy resin with a cylinder of 60 mm high and 15 mm diameter. Before treatment, the cylinder head surface was cleaned, and a thermoplastic primer composition was applied and dried. A comparative sample without primer treatment was also prepared. Then an adhesive composition was prepared and 0.5 g to 1.0 g was applied to the substrate. A second substrate was applied, and the flat surfaces of the substrates were bonded together by curing at 23 ° C for 7 days. The cross tensile strength was measured by an Instron tensile tester.

[0032] The detachment test was performed using a laboratory established qualitative method, the process is as follows:

[0033] 1) Clean the substrate surface (100 mm*150 mm*2 mm) by wiping with ethanol.

[0034] 2) The substrate was then coated with a primer by brush and allowed to dry. Comparative samples were also prepared without primer treatment.

[0035] 3) Prepare a thermosetting adhesive layer by combining Part A and Part B of the 2K PU adhesive in a high speed mixer at 1,000 rpm for 1 minute.

[0036] 4) Approximately 10 to 15 g of adhesive was applied to the substrate using two 1 mm diameter copper wires to control the layer thickness.

[0037] 5) The second substrate was then stacked lengthwise. The bonding surfaces of the substrates were then contacted and held in place with clips. The adhered substrates were then cured at 23°C for 7 days.

[0038] 6) Before the release test, the samples were heated in an oven at 80°C for 10 minutes.

[0039] 7) The sample was then removed and secured by a curved clamp while the substrate was manually pried off using a screwdriver. Detachment within 1 minute was considered "successful". "Failure" was indicated by two modes: cohesive failure (adhesive on both sides after detachment) and adhesive failure (adhesive on one side after detachment).

[0040] Example

[0041] The following examples are provided to illustrate embodiments of the present invention and are not intended to limit the scope of the present invention. Unless otherwise specified, all parts and percentages are by weight. Table 2 lists the materials used in the following examples:

[0042]

[0043] Example 1: Effect of primer resin type on performance

[0044] In this example, multilayer composition samples were prepared on epoxy-coated Type 3 aluminum substrates that were first coated with different types of thermoplastic primer compositions. The substrates were then bonded with a thermosetting 2K PU structural adhesive, aged, and tested for cross-tensile strength and releasability. For comparison, epoxy-coated Type 3 substrates that were not primed were also used in the testing.

[0045] The results are summarized in Table 3. The data in parentheses represent the percent reduction in strength of the examples compared to a control sample having no thermoplastic primer layer at 23°C.

[0046]

[0047] Example 1 shows that the polarity of the primer resin affects the adhesion and release properties, specifically, reducing the polarity of the primer increases the release at higher temperatures (e.g., >50°C) but reduces the bond strength at room temperature, while increasing the polarity of the primer resin (e.g., TPU, PET) maintains room temperature adhesion and does not improve the release performance at high temperatures.

[0048] Regarding CE1, when bonded with a thermosetting adhesive without primer treatment, the cross tensile strength of the sample decreased from 22 MPa to 3.7 MPa as the temperature increased from 23° C. to 90° C. However, the release test results showed an inability to release and a cohesive failure mode within the thermosetting adhesive layer.

[0049] Samples CE3-CE8 bonded to lower polarity thermoplastic resin based primers and thermosetting adhesives showed a reduction in cross tensile strength at 23°C or 90°C compared to CE1, potentially indicating that the lower polarity of the primer layer composition adversely affects the bonding performance with the polar thermosetting adhesive. For the comparative samples, the reduction in cross tensile strength at 23°C exceeded 30% and indicated that the reduced polarity thermoplastic primer layer had poor compatibility with the thermosetting adhesive and reduced the overall bond strength to unacceptable levels. In practice, this was demonstrated by adhesive failure at the interface of the substrate / primer layer and / or primer layer / adhesive layer while the adhesive layer remained intact.

[0050] Regarding CE9-CE12, the samples bonded with the polar thermoplastic resin based primer and polar thermosetting adhesive are shown in Table 3 to have cross tensile strengths comparable to that of CE1 without primer treatment at 23°C and 90°C. CE9-CE12 are characterized by cohesive failure, indicating that the polar thermoplastic resin based primer layer does not increase releasability at high temperature.

[0051] Sample IE1 containing a MAH-g-CPO based primer exhibited a minor reduction of 8.2% in cross tensile strength at 23°C compared to CE1 without a thermoplastic primer layer. However, at 90°C, IE1 exhibited a cross tensile strength of 2.3 MPa (a reduction of -37% compared to CE1) and achieved successful detachment. The reduction in cross tensile strength at elevated temperatures was also associated with the adhesive failure mode. Thus, the thermoplastic primer layer incorporating MAH-g-CPO exhibits a polar balance with epoxy coated Al and 2K PU thermoset adhesives characterized by suitable bonding properties at low temperatures and detachability at high temperatures.

[0052] Example 2: Effect of Thermoplastic Resin on the Performance of MAH-g-CPO-Based Primers

[0053] In the next example, the release performance of primer layer formulations containing MAH-g-CPO and blends with polymers of different polarities were tested on epoxy coated Type 3 Al substrates. The samples were prepared essentially as described for Example 1. The data in parentheses represent the percent reduction in strength of the examples compared to the control sample without a primer layer at 23°C.

[0054]

[0055]

[0056] When different dosages of hydrogenated rosin were introduced into the MAH-g-CPO based primer, IE2 (4.5 wt% MAH-g-CPO and 0.5 wt% hydrogenated rosin) and IE3 (3.5 wt% MAH-g-CPO and 1.5 wt% hydrogenated rosin) showed that the inclusion of 0.5 wt% to 1.5 wt% hydrogenated rosin into the primer formulation (<50 wt% based on the solids of the primer) provided acceptable cross tensile strength at room temperature and acceptable release performance at elevated temperatures. Similarly, good adhesion and release properties were obtained with a 3.5:1.5 mixture of MAH-g-CPO and TPU (IE4) and a mixture of MAH-g-CPO and MAH-g-EVA (IE5).

[0057] Example 3: Effect of substrate on release performance

[0058] In the next example, different substrates (epoxy coated Al, Type 3 Al) were coated with a thermoplastic primer composition for IE3 (3.5 wt% MAH-g-CPO + 1.5 wt% hydrogenated rosin) and bonded with a 2K PU thermoset adhesive. The samples were prepared essentially as described for Example 1. Lap shear strength, cross tensile strength, and peel tests were performed. The results are summarized in Table 5. The cross tensile strength, lap shear strength, and peel test results indicate peeling on Type 3 Al, with ease of peeling being Type 3 Al > Epoxy coated Al.

[0059]

[0060]

[0061] Example 4: Effect of primer layer thickness on performance

[0062] In this example, samples were measured that had solid thermoplastic primer layers of varying thickness on epoxy-coated Al substrates that were then bonded with a thermosetting adhesive. The thermoplastic primer layer thickness was controlled by varying the solids content and / or using multiple layers of thermoplastic primer. The samples were prepared essentially as described for Example 1. The results are summarized in Table 6.

[0063]

[0064] Example 4 shows that when the thickness of the dried thermoplastic primer layer is less than 10 μm, the lap shear strength and cross tensile strength of CE16 and CE17 are reduced compared to CE1 without primer treatment. However, when the thickness of the dried thermoplastic primer layer exceeds 10 μm, the performance of IE6-IE9 meets the target adhesion and release properties. However, the selected multi-layer composition shows an upper limit of effectiveness at higher layer thicknesses. For example, when the thickness of the dried solid primer layer is about 80 μm, the CE18 data shows that the cross tensile strength at room temperature is reduced by 76.1% compared to CE-1 without a thermoplastic primer layer.

[0065] While the foregoing is directed to illustrative embodiments, other and further embodiments may be devised without departing from the basic scope of the present invention, which is defined by the claims that follow.

Claims

1. A multilayer composition comprising: A substrate having a surface energy of 35 dynes / cm or greater; One or more thermoplastic primer layers comprising 55 wt % to 100 wt % of a maleic anhydride grafted chlorinated polyolefin and having a glass transition temperature in the range of 50° C. to 120° C.; and one or more thermosetting adhesive layers.

2. The multi-layer composition of claim 1, wherein the maleic anhydride grafted chlorinated polyolefin has a maleic anhydride grafting degree greater than 1% and a chlorination content greater than 10%.

3. The multi-layer composition of claim 1, wherein the maleic anhydride grafted chlorinated polyolefin has a glass transition temperature of 60°C to 80°C.

4. The multi-layer composition of claim 1, wherein the one or more thermoplastic primer layers further comprise up to 45 wt % of one or more additional thermoplastic polymers, and wherein the one or more thermoplastic primer layers have a glass transition temperature of 50° C. to 100° C.

5. The multi-layer composition of claim 1, wherein the one or more thermoplastic primer layers further comprise one or more additional thermoplastic polymers selected from the group consisting of maleic anhydride grafted polyolefin (MAH-g-POE), polyolefin (POE), maleic anhydride grafted ethylene-vinyl acetate (MAH-g-EVA), ethylene-vinyl acetate (EVA), maleic anhydride grafted styrene-ethylene-butylene-styrene (MAH-g-SEBS), hydrogenated rosin, thermoplastic polyurethane (TPU), or polyester (PET).

6. The multi-layer composition of claim 1, wherein the multi-layer composition has a reduction in cross-tension strength at 23°C of less than 30% relative to a comparative multi-layer composition without the one or more thermoplastic primer layers.

7. A method of releasing the multilayer composition according to claim 1, the method comprising: heating the multilayer composition to a temperature greater than 50° C.; and removing at least one of the layers of the multi-layer composition. 8 . An electric vehicle battery assembly comprising the multilayer composition according to claim 1 .